Neuromuscular Junction as an Entity of Nerve-Muscle Communication - Elisa Lepore; Irene Casola; Gabriella Dobrowolny; Antonio Musarò (Cells, 2019)
One of the crucial systems severely affected in several neuromuscular diseases is the loss of effective connection between muscle and nerve, leading to a pathological non-communication between the two tissues. The neuromuscular junction (NMJ) represents the critical region at the level of which muscle and nerve communicate. Defects in signal transmission between terminal nerve endings and muscle membrane is a common feature of several physio-pathologic conditions including aging and Amyotrophic Lateral Sclerosis (ALS). Nevertheless, controversy exists on whether pathological events beginning at the NMJ precede or follow loss of motor units. In this review, the role of NMJ in the physio-pathologic interplay between muscle and nerve is discussed.